التجارة الإلكترونية وسلاسل الإمداد الرقمي - بن سكحال،هدية; حساني ،حسين (جامعة الوادي University of Eloued, 2024)
تهدف هذه الورقة البحثية إلى التعرف على كل من التجارة الإلكترونية وسلاسل الإمداد الرقمي من خلال تحليل العلاقة القائمة بين المتغرين في شركة "شي إن" باعتبارها من الشركات الرائدة في مجال الموضة التي اعتمدت الرقمنة في جميع تعاملاتها، تم اعتماد المنهجية الوصفية في التعريف بالمتغيرات وتحليلها، توصلنا إلى مجموعة من النتائج من بينها: وجود علاقة إيجابية تكاملية بين التجارة الإلكترونية وسلاسل الإمداد الرقمي باعتبار الأولى حجر الأساس الذي تقوم عليه الرقمنة، كما تم اقتراح اعتماد نظامين في الجزائر الأول محلي في التجارة خاص بالمتعاملين الصغار والآخر عالمي خاص بالشركات الكبرى كمرحلة أولية، للمساهمة في بناء بنى تحتية رقمية ذات جاهزية إلكترونية شاملة لكل المجالات والميادين بالشراكة بين كل من القطاعين العام والخاص قبل إعتماد نظام رقمي مفتوح كليا ليواكب الاقتصاد الرقمي العالمي الذي يسمح برقمنة سلاسل الإمداد مستقبلا بدون مخاطر. This research paper aims to identify E-commerce and digital supply chains by analyzing the relationship between expatriates in Shein. This leading fashion company has used digitalization in all its dealings. A descriptive methodology was adopted to define the variables and study the relationship between them in Shein. We reached a set of results, including There is a positive, complementary relationship between e-commerce and digital supply chains, as the former is the basis. It was also suggested to adopt two systems in Algeria, the first local in trade for small trades and the other global for large companies as in the initial stage to contribute to building digital infrastructures with comprehensive electronic readiness for all fields and areas in partnership between the public and private sectors before adopting a completely open digital system to keep pace with the global economy that allows for the digitization of supply chains in the future without risks
E-commerce & digital supply chains: Shein as a case study
Keywords: التجارة الإلكترونية; سلاسل الإمداد الرقمي; الرقمنة; E-commerce; digital supply chains; digitization